Performance of partial nitrification process in a zeolite biological aerated filter with the addition of sulfamethoxazole. (May 2022) - Zhang, Tianyi; Xu, Wenjie; Kang, Pengfei; Guo, Xiaoying; Li, Haisong; Wang, Yan; Wan, Junfeng
Abstract: Due to the rapid development of medical industries, wastewater treatment plants have become sinks for residual antibiotics. However, the contribution of novel partial nitrification processes to the bioremediation of antibiotics remains unclear. In this study, the removal rate of a partial nitrification process on the biotransformation of sulfamethoxazole (SMZ) was evaluated. A biological aerated filter made from zeolite successfully achieved stable partial nitrification. A nitrite accumulation percentage (NAP) greater than 85% was obtained when the influent ammonium concentration was increased to 300 mg/L with a nitrogen loading rate of 1.24 kg/(m 3 d). Batch tests were performed on support collected from different heights of the up-flow reactor at the end of the pilot monitoring experiment. The maximum ammonium oxidation rate of 5.63 mg/(g VSS·L) in one hour was recorded at a height of 0.32–0.48 m in the reactor, indicating nitrifying bacteria activity link between the free ammonia (FA) and biomass concentration was found. After the addition of SMZ (2.5 mg/L), the NAP declined to approximately 70%, and the abundance of Nitrosomonas (the main ammonia oxidizing bacteria (AOB) genus in the zeolite biological aerated filter (ZBAF)) decreased 7.24–6.10%. Lower abundance and activity of AOB oxidized ineffectively the primary amine of SMZ, which led to lower than 19% of the SMZ removal efficiency. Graphical Abstract: ga1 Highlights: AOB was successfully enriched in a zeolite biological aerated filter. Stable partial nitrification achieved with influent ammonium concentration of 300 mg/L. The effect of FA inhibition on NOB was related to dose of FA and the biomass concentration. Microbial analysis showed that SMZ reduced the abundance of AOB in the reactor.